2022
DOI: 10.3390/nano13010149
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic Effectiveness of Thiourea-Reduced Graphene Oxide on Human Lung Cancer Cells and Fungi

Abstract: This study demonstrated the effective reduction of graphene oxide (GO) by employing thiourea as a reducing and stabilizing agent. Two fungi (Aspergillus flavus and Aspergillus fumigatus) were used for anti-fungal assay. Cell viability, cell cycle analysis, DNA fragmentation, and cell morphology were assessed to determine the toxicity of thiourea-reduced graphene oxide (T-rGO) on human lung cancer cells. The results revealed that GO and T-rGO were hazardous to cells in a dose-dependent trend. The viability of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Our study of anticancer activity showed 21% for Ti/GO-NPs at 150 µg/mL. Other similar studies showed that lung cancer cells treated with GO showed anticancer activity of 21.69% at 1000 µg/mL [36]. The anticancer activity responds to the lung cancer cells in a dose-dependent manner with cell viability, as the concentration of the nanoparticles increases the cancer cell viability decreases.…”
Section: Discussionsupporting
confidence: 69%
“…Our study of anticancer activity showed 21% for Ti/GO-NPs at 150 µg/mL. Other similar studies showed that lung cancer cells treated with GO showed anticancer activity of 21.69% at 1000 µg/mL [36]. The anticancer activity responds to the lung cancer cells in a dose-dependent manner with cell viability, as the concentration of the nanoparticles increases the cancer cell viability decreases.…”
Section: Discussionsupporting
confidence: 69%
“…Therefore, meticulous efforts have been undertaken to delve into the intricacies of cancer development, diagnosis, and treatment, as the human race strives to overcome this obstinate adversary. As research on the relationship between fungi and cancer continues to deepen, there has been a growing interest in exploring this area [ [5] , [6] , [7] , [108] , [109] , [110] ]. Here, we further analyzed the following aspects related to the research on fungi and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is a primary reason of death globally, accounting for over 10 million deaths in 2020, or roughly one in every six deaths [ [1] , [2] , [3] , [4] , [5] ]. Prostate cancer is the most prevalent cancer among men and the second leading cause of cancer mortality after skin cancer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%